DENGUE PREVENTION AND PUBLIC PERCEPTION OF BARRIERS TO ELIMINATE MOSQUITO BREEDING SITES AMONG MALAYSIANS - Jasman, Noorlaile; Farhana, Siti Nur; Saleh, Kamarul Zaman; Jaafar, Norrafizah; Zaini, Zanariah; Krishnan Kaundan, Manimaran; Joslyn Panting, Albeny (The Indonesian Journal of Public Health, 2024)
Introduction: Malaysia reported a 150.7% increment in dengue cases in 2022 compared to 2021. Aim of this study was to evaluate the respondent's involvement in dengue prevention initiatives and public perceptions of barriers to eliminating mosquito breeding sites among Malaysian residents. Methods: A cross-sectional survey employing a population-based approach and a sophisticated survey design, carried out from August to October 2020. Respondents in this study must be 13 years of age or older from the selected households and live in non-institutionalized living quarters (LQ) units in Malaysia, regardless of citizenship. A pretested and structured Self-administered questionnaire (SAQ) was used. SPSS Version 23.0 was used to analyse the data. Results: Out of 4,522 participants, only 1,642 (36.7%) people carried out individual "Search and Destroy" mosquito breeding site practices at home once a week as recommended by the Malaysian Ministry of Health (MOH). Most respondents (n = 3,831, 94.3%) said they cleared their homes' clogged drains and cleaned their rain gutters. There  is  a significant association between compliance of ‘Search and Destroy’ practicing and type of house (p-value  =  0.001). In order to avoid getting bitten by mosquitoes, 89.9% of the respondents (n=4,047) stated that they stay indoors when  Aedes mosquito are active. The perceived barriers to dengue prevention activities are high for 22.6% of the participants. Conclusions: Addressing public perception of barriers to dengue prevention is an important step in controlling the spread of this disease in Malaysia.